INFORMATION SCIENCE AND COMMUNICATION SCIENCE: “another one dialogue interdisciplinary” - Linares Columbié, Radamés (Informação em Pauta, 2018)
The diversity of discourses that the processes of organization, production and diffusion of knowledge express is examined. Establish features identifiers of the Information Science and Communication Science. You discuss interdisciplinary's proposals that characterize the bodies of knowledge that are studied. The character needs the existent dialogues between of the Information Science and Communication Science. You include bibliographic references and a proposal of findings.